2005
DOI: 10.1093/her/cyh038
|View full text |Cite
|
Sign up to set email alerts
|

Employee's perceived exposure to environmental tobacco smoke, passive smoking risk beliefs and attitudes towards smoking: a case study in a university setting

Abstract: Despite the growing literature on workplace smoking policies, few studies have focused on the implementation of such policies in university settings. Smoking in the workplace is still very common in many countries, including Spain. While the law is about to change and more non-smoking policies are to be implemented, it is not clear what kind of restrictions Spanish workers would find acceptable. This study investigated perceived exposure to environmental tobacco smoke (ETS), passive smoking risks beliefs and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…In addition, we observed that the only tobacco control policy statement on which knowledge differed among the 3 smoking status groups was the health hazards of exposure to SHS in the workplace, where a significantly lower proportion of current smokers agreed with the statement compared to the other two groups (ex and never smokers). This is consistent with the findings of Duaso et al 2006, who compared the beliefs of smokers and non-smokers on the risks of SHS and found that perceived risks were significantly higher among non-smokers [20]. …”
Section: Discussionsupporting
confidence: 92%
“…In addition, we observed that the only tobacco control policy statement on which knowledge differed among the 3 smoking status groups was the health hazards of exposure to SHS in the workplace, where a significantly lower proportion of current smokers agreed with the statement compared to the other two groups (ex and never smokers). This is consistent with the findings of Duaso et al 2006, who compared the beliefs of smokers and non-smokers on the risks of SHS and found that perceived risks were significantly higher among non-smokers [20]. …”
Section: Discussionsupporting
confidence: 92%
“…SFH restrictions are more common among those with children in the home (especially children less than 5 years old21 and with non-smoking family members in the home 22. Increased knowledge and perception of the harms of SHSe are also shown to be associated with more favourable attitudes towards smoke-free environments,23 better efforts to reduce exposure24 25 and adoption of complete SFH restrictions 16 20. Indeed, Georgia-based research indicates that, while the majority of adults believe that SHSe is harmful, homes continue to be a primary source of SHSe15 and common efforts to reduce its impact include partial restrictions (eg, limiting rooms where smoking is allowed) 26.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the adverse health effects of SHS exposure is an especially important factor shaping public attitudes towards smoke-free policies [ 21 ]. Research indicates that increased knowledge about the harmfulness of SHS is associated with greater efforts to minimize exposure [ 22 , 23 ], reduced SHS exposure among both smokers and nonsmokers [ 22 – 24 ], and adoption of smoke-free home rules [ 25 , 26 ]. Increased awareness of the adverse health effects of SHS exposure is also associated with lower smoking initiation among youth [ 27 ] and more favorable attitudes toward smoke-free environments [ 1 , 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%